2009
DOI: 10.1002/chem.200900822
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Complexes of Simple Anions with Electron‐Deficient Arenes: Spectroscopic Evidence for Two Types of Structural Motifs for Anion–Arene Interactions

Abstract: Anion-pi interactions between a pi-acidic aromatic system and an anion are gaining increasing recognition in chemistry and biology. Herein, the binding features of an electron-deficient aromatic system (1,3,5-trinitrobenzene (TNB)) and selected anions (OH-, Br-, and I-) are examined in the gas phase by using the combined information derived from collision-induced dissociation experiments at variable energy, infrared multiple-photon dissociation spectroscopy, and quantum chemical calculations. We provide spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 83 publications
(92 reference statements)
2
38
0
1
Order By: Relevance
“…That interactions of simple anions with phenyl hydrogens are preferred energetically over the face of fluorinated benzenes has been demonstrated spectroscopically. [81] Similarly, both Mascal and coworkers [82] and Hay et al [83] showed computationally that interactions of simple anions with aryl hydrogens are more enthalpically favorable than anion/p complexes. Further complicating discussions of anion/p interactions is the existence of favorable complexes in which the anion forms a covalent (or partially covalent) bond with an aryl carbon (Meisenheimer complexes), which are often competitive with anion/p interactions.…”
Section: Anion/p Interactionsmentioning
confidence: 94%
“…That interactions of simple anions with phenyl hydrogens are preferred energetically over the face of fluorinated benzenes has been demonstrated spectroscopically. [81] Similarly, both Mascal and coworkers [82] and Hay et al [83] showed computationally that interactions of simple anions with aryl hydrogens are more enthalpically favorable than anion/p complexes. Further complicating discussions of anion/p interactions is the existence of favorable complexes in which the anion forms a covalent (or partially covalent) bond with an aryl carbon (Meisenheimer complexes), which are often competitive with anion/p interactions.…”
Section: Anion/p Interactionsmentioning
confidence: 94%
“…Gas phase spectroscopic evidence of these two types of structural motifs supports this relationship [23]. The amount of interaction between the electrons of the anion and the л-system is enhanced and stabilized by electron deficiencies in the aromatic ring.…”
Section: Introductionmentioning
confidence: 80%
“…Thus, IRMPD spectroscopy has provided for the first time conclusive evidence for the existence of Meisenheimer complexes in the gas phase (see Fig. 2 with X = H and Y = OH, OCH 3 , OC 2 H 5 ) [23,24].…”
Section: Interaction Of Anions With π-Acidic Aromatics: Direct Evidenmentioning
confidence: 97%
“…X-ray diffraction data have been reported showing that in the crystal structure a halide is placed over the periphery of the ring of strongly electron deficient arenes. Geometrical features that characterize the TNB-Brcomplex 4 are an elongated C-Br bond (2.67 Å) if compared with a typical covalent C-Br bond length (1.93 Å) and a H-C-Br angle close to 90° while the carbon atom closest to Br is not appreciably distorted from the original sp 2 -type geometry [23]. Forcing this carbon to attain a tetrahedral coordination, as in a strongly covalent anionic σ-complex 5, and constraining the C-Br distance to 1.93 Å yields a structure noticeably higher in energy relative to 4 that is not a stationary point on the potential energy surface.…”
Section: Strongly To Weakly Covalent σ-Interaction In the Negatively mentioning
confidence: 99%
See 1 more Smart Citation